Dissecting PTPN7‐driven aggressiveness in IDH‐wildtype astrocytomas: multi‐omics, clinical validation, and spatial transcriptomics for prognostic insights - Tung Liu; Yu-Chieh Lin; Pei-Chi Chang; Dueng-Yuan Hueng; Yao-Feng Li (Discover Oncology)
Abstract Background Gliomas, particularly IDH‐wildtype astrocytomas, remain highly aggressive and resistant to current therapies. Despite advances in molecular classification, effective therapeutic targets are still limited. Consequently, identifying new targets is essential to improve patient survival. PTPN7, a tyrosine phosphatase implicated in MAPK signaling, is known to play roles in various malignancies but remains underexplored in gliomas. This study examines the prognostic significance, spatial distribution, and immune‐related functions of PTPN7, aiming to elucidate its potential as a prognostic role and therapeutic target in glioma treatment. Materials and methods We analyzed PTPN7 mRNA expression in gliomas via TCGA, CGGA, and single‐cell RNA sequencing (GSE131928 and GSE89567). Kaplan determined prognostic significance–Meier and uni‐/multi-variate Cox survival analyses. Gene set enrichment analysis (GSEA) was used to identify dysregulated pathways, immune signatures, and cell‐type enrichments. We also applied CIBERSORT to evaluate the relationships between PTPN7 expression and 12‐principal cell states and 22 immune populations. Spatial transcriptomics (Ivy Glioblastoma Atlas, 10 × Genomics Visium) mapped PTPN7 distribution; these findings were corroborated by immunohistochemistry‐validated protein expression in 70 cases. Results Pan‐cancer analysis revealed PTPN7 overexpression in multiple malignancies, including glioma. Notably, PTPN7 was significantly elevated in IDH‐wildtype astrocytomas, correlating with higher tumor grades and poorer overall survival. GSEA indicated that high PTPN7 is linked to T‐cell differentiation, macrophage/monocyte activation, and dendritic cell-associated pathways. Both immune deconvolution and single‐cell analyses showed that PTPN7 positively correlates with myeloid series and T‐cell populations, supported by additional GSEA findings. In the Ivy dataset and spatial transcriptomics, PTPN7 was concentrated in peri‐necrotic, cellular tumor, and slightly lower in the infiltrating border regions, consistent with immune interaction sites. Immunohistochemical data further demonstrated high PTPN7 expression tracks with increased tumor grade, reaching statistical significance in IDH‐wildtype astrocytomas and confirming its clinical relevance. Conclusion This study positions PTPN7 as a prognostic biomarker and immune modulator in gliomas, particularly IDH‐wildtype astrocytomas. Its expression correlates with tumor aggressiveness and immune infiltration, potentially driving glioma progression. Targeting PTPN7 may disrupt immune evasion and support tumor eradication, indicating a promising therapeutic avenue in immunotherapy‐based strategies.